Autosomal Recessive Primary Microcephaly (MCPH): An Update - Zaqout, Sami; Morris-Rosendahl, Deborah; Kaindl, Angela M. (Neuropediatrics, 2017)
Autosomal recessive primary microcephaly (MCPH; MicroCephaly Primary Hereditary) is a genetically heterogeneous neurodevelopmental disorder characterized by a significantly reduced head circumference present already at birth and intellectual disability. Inconsistent features include hyperactivity, an expressive speech disorder, and epilepsy. Here, we provide a brief overview on this rare disorder pertinent for clinicians.
Keywords: MCPH; microcephaly; intellectual disability